Optimalisasi Keterampilan Berpikir Kritis Dalam Pembelajaran Bahasa Indonesia Melalui Deep Learning Di Sekolah Dasar - Rahmita Rahmita (Jurnal Sultra Elementary School, 2025)
Era of technological disruption demands the emergence of a generation that is not only able to process information but also possesses critical thinking skills. Indonesian Language learning in elementary schools has great potential to serve as the foundation for developing these skills. However, in reality, learning practices in schools often remain focused on memorization and lower-order thinking, which do not sufficiently challenge students’ analytical and evaluative abilities. This study aims to explore strategies for optimizing critical thinking skills in the context of Indonesian Language learning in elementary schools through the implementation of a Deep Learning approach. Deep Learning, which emphasizes deep understanding, conceptual connections, and reasoning, is believed to create meaningful learning experiences. The research method used is a literature study by analyzing various academic sources such as journals, books, and scientific articles published between 2020 and 2025. The findings reveal that Deep Learning can be integrated through several strategies, including: (1) the use of essential questions that stimulate inquiry, (2) the implementation of contextual project-based learning, (3) the utilization of multimodal texts to analyze multiple perspectives, (4) the practice of digital literacy to enhance students’ ability to evaluate the credibility of information, and (5) authentic assessment that measures the process of thinking. The conclusion of this study is that the integration of Deep Learning principles into Indonesian Language learning provides an effective framework for cultivating critical thinking habits from an early age, ultimately preparing students to become lifelong learners and responsible digital citizens..